THE EFFECT OF LIQUID TOFU WASTE AND GROWING MEDIA ON THE GROWTH AND YIELD OF LONG BEANS (Vigna sinensis L.) - Nindi Fauziah (Jurnal Bioteknologi dan Biosains Indonesia, 2022)
Long bean is a leguminous plant that has the potential to be developed into productive plants. Tofu liquid waste organic fertilizer and planting media are needed to meet nutrient needs, improve the physical and chemical properties of the soil. This study aims to understand the effect of liquid tofu waste, growing media, and their combined interaction on the growth and yield of long beans. This study used a factorial randomized block design (RBD) with 3 replications, 3 treatments of liquid tofu waste of 0 mL (T0), 150 mL (T1), and 300 mL (T2), and 3 planting media, namely cow manure compost + rice husk charcoal (M1), cow manure compost + cocopeat (M2), and cow manure compost + chopped fern (M3). If they had a significant effect, a Tukey's test at a 5% probability level would be performed. The parameters observed included the chlorophyll a and b, net assimilation rate, relative growth rate, height, number of flowers, pod length, and wet fruit weight of long beans. The results showed that the T1 and M3 treatments significantly affected chlorophyll a and b, height, number of flower, and pod length. The T1 and M2 treatments significantly affected the wet fruit weight of long beans.The T2 and M2 treatments significantly affected the net assimilation rate. Finally, the T2 and M3 treatments significantly affected the relative growth rate. There was no interaction effect found between liquid tofu waste and growing media on all research parameters.